(untitled) (Prostor, 2021)
This paper is studying influence of new technologies on city development with accent on socio-spatial dimension. The primary goal of the paper is to point out the reflections of earlier ideas in the context of modern technological processes in cities. All social, technical and technological components of a community, and finally civilization, are reflected within space of the city. Although having remained the greatest consumer of many material goods, city has also become a ‘’producer’’ of many technical-technological and spiritual values of civilization. Taking into account acceleration of phenomena in the world of technology and technology featuring modernity, it reasonably brings a question on realistic chance for prediction of their further course and related social changes that are about to cause it. In many scenarios of urban future, one can sense the idea of a city as a result of high technological achievements of civilization. Special attention is paid on informational city which, connecting a lot of people into systems of interactive information technology change the way of their mutual communication, as well as their social life and culture of behaviour. Measure of organization and function of city is set by telecommunication technologies, information, and computers. If city is a ‘’print of a society in space’’, then a contemporary moment refers to ‘’digitalization’’ of human beings, digitalization of their interactions, new aesthetics, value and other criteria. The tendency of this paper is to contribute to the understanding of new technologies on 21st century cities interpreted primarily through the prism of certain theoretical and experimental ideas and concepts of the 20th century.